85.0k views
2 votes
-7/9x-5/36x+1/4x= -48 help

User TheWebs
by
4.8k points

1 Answer

3 votes

Answer:

x = 72

Explanation:


(-7)/(9)x-(5)/(36)x+(1)/(4)x=-48

Step 1: Simplify both sides of the equation.


(-7)/(9)x-(5)/(36)x+(1)/(4)x=-48


(-7)/(9)x+(-5)/(36)x+(1)/(4)x=-48


((-7)/(9)x+(-5)/(36)x+(1)/(4)x)=-48 (Combine Like Terms)


(-2)/(3)x=-48


(-2)/(3)x=-48

Step 2: Multiply both sides by
((3)/(-2) )


((3)/(-2))*((-2)/(3)x)=((3)/(-2))*(-48)


x=72

Therefore,
x=72 is your final answer.

User Rredondo
by
6.0k points